2020
DOI: 10.5614/3bio.2020.2.1.1
|View full text |Cite
|
Sign up to set email alerts
|

The effect of Paraquat Dichloride application on diversity and abundance of soil arthropods in the corn field

Abstract: We investigated the effect of paraquat dichloride herbicide application on diversity and abundance of soil arthropods in a corn field. In addition to control (0 mL/L), four concentrations of paraquat dichloride were applied i.e. 3.33 mL / L, 4 mL / L, 4.66 mL / L and 5.33 mL / L. Sampling was carried out four times, namely at T0 (before tillage), T1 (after tillage), T2 (after spraying herbicides), and T3 (before harvesting) using a pitfall trap method. Soil arthropod samples were identified to the family level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…The herbicide PC was found to have no significant effect on soil arthropods according to Anggraeni et al (2020). Similarly, Martono et al (2021) reported that PC application in rice paddy soil did not greatly impact soil fauna, including arthropods and earthworms.…”
Section: Population Dynamics Of Bacteriamentioning
confidence: 99%
“…The herbicide PC was found to have no significant effect on soil arthropods according to Anggraeni et al (2020). Similarly, Martono et al (2021) reported that PC application in rice paddy soil did not greatly impact soil fauna, including arthropods and earthworms.…”
Section: Population Dynamics Of Bacteriamentioning
confidence: 99%